Water mass interaction in the confluence zone of the Daning River and the Yangtze River—a driving force for algal growth in the Three Gorges Reservoir - Holbach, Andreas; Wang, Lijing; Chen, Hao; Hu, Wei; Schleicher, Nina; Zheng, Binghui; Norra, Stefan (Environmental science and pollution research international, 2013)
Increasing eutrophication and algal bloom events in the Yangtze River Three Gorges Reservoir, China, are widely discussed with regard to changed hydrodynamics and nutrient transport and distribution processes. Insights into water exchange and interaction processes between water masses related to large-scale water level fluctuations in the reservoir are crucial to understand water quality and eutrophication dynamics. Therefore, confluence zones of tributaries with the Yangtze River main stream are dedicated key interfaces. In this study, water quality data were recorded in situ and on-line in varying depths with the MINIBAT towed underwater multi-sensor system in the confluence zone of the Daning River and the Yangtze River close to Wushan City during 1 week in August 2011. Geostatistical evaluation of the water quality data was performed, and results were compared to phosphorus contents of selective water samples. The strongly rising water level throughout the measurement period caused Yangtze River water masses to flow upstream into the tributary and supply their higher nutrient and particulate loads into the tributary water body. Rapid algal growth and sedimentation occurred immediately when hydrodynamic conditions in the confluence zone became more serene again. Consequently, water from the Yangtze River main stream can play a key role in providing nutrients to the algal bloom stricken water bodies of its tributaries.